Sildenafil exposure in neonates with pulmonary hypertension after administration via a nasogastric tube. Issue 2 (30th November 2009) - Ahsman, Maurice J; Witjes, Bregje C; Wildschut, Enno D; Sluiter, Ilona; Vulto, Arnold G; Tibboel, Dick; Mathot, Ron A
Abstract : Objective: To describe the pharmacokinetics and exposure of oral sildenafil (SIL) in neonates (2–5 kg) with pulmonary hypertension (PH). Design: We included 11 neonates (body weight 2–5 kg, postnatal age 2–121 days) who received SIL and extracorporeal membrane oxygenation (ECMO) treatment for PH. SIL capsules were given via a nasogastric tube. Blood samples were collected via a pre-existing arterial line to quantify SIL and metabolite plasma levels (219 samples). Non-linear mixed effects modelling was used to describe SIL and desmethylsildenafil (DMS) pharmacokinetics. Results: A one-compartment model was suitable for SIL and DMS. Interpatient and intrapatient variability for clearance at 100% bioavailability were 87% and 27% (SIL) and 62% and 26% (DMS). Patient weight, postnatal age and post-ECMO time did not explain variability. Concomitant fluconazole use was associated with a 47% reduction in SIL clearance. The exposure expressed as average plasma concentration area under the curve over 24 h (AUC24 (SIL+DMS) ) ranged from 625 to 13 579 ng/h/ml. An oral dose of 4.2 mg/kg/24 h would lead to a median AUC24 (SIL+DMS) of 2650 ng/h/ml equivalent to 20 mg three times a day in adults. Interpatient variability was large, with a simulated AUC24 (SIL+DMS) range (10th and 90th percentiles) of 1000–8000 ng/h/ml. Conclusions: SIL pharmacokinetics are highly variable in post-ECMO neonates and infants. In a median patient, the current dose regimen of 0.5–2.0 mg/kg four times a day leads to an exposure comparable to the recommended adult dose of 20 mg four times a day. Careful dose titration, based on efficacy and the occurrence of hypotension, remains necessary. Follow-up research should include appropriate pharmacodynamic endpoints, with a population pharmacokinetic/pharmacodynamic analysis to assign a suitable exposure window or target concentration.